Low-Dose Vitamin D Protects Hyperoxia-Induced Bronchopulmonary Dysplasia by Inhibiting Neutrophil Extracellular Traps - Chen, Cuie; Weng, Huachun; Zhang, Xixi; Wang, Shi; Lu, Chaosheng; Jin, Hongxing; Chen, Shujun; Liu, Yuanyuan; Sheng, Anqun; Sun, Yuanyuan (Frontiers in Pediatrics, 2020)
Background and Objective: As bronchopulmonary dysplasia (BPD) can lead to considerable mortality and morbidity, this disease is the focus of attention in neonatology. Vitamin D (VD) , which has anti-inflammatory properties and promotes lung growth, may have a therapeutic effect on BPD. Neutrophil extracellular traps (NETs) overexpression were demonstrated to be involved in the pathogenesis of BPD in our previous study. This study aimed to elucidate the effect of VD on BPD and the role of NETs in this process. Methods: Newborn rats were exposed to 90% oxygen continuously for 7 days to mimic BPD, and rats under hyperoxia were injected with 1,25(OH)2D3 at different doses (0.5 ng/g, 3 ng/g). Alveolarization, pulmonary vascular development, inflammatory cytokines and NETs were assessed. Results: Hyperoxia increased mortality, decreased body weight, impaired alveolarization with a decrease in radial alveolar count (RAC) and an increase in mean linear intercept (MLI), and impaired vascular development with low expression of vascular endothelial growth factor (VEGF). Meanwhile, hyperoxia enhanced expression of the proinflammatory factors TNF-α, IL-1β and IL-6, and elevated NETs in lung tissues and plasma. Low-dose VD (0.5 ng/g) administration increased the survival rate, attenuated developmental retardation, improved alveolarization and pulmonary vascular development in hyperoxia-induced BPD, and reduced the expression of proinflammatory factors and NETs. However, high-dose VD (3 ng/g) treatment did not attenuate lung injury or NETs significantly, and even lead to more severe developmental retardation and a higher mortality rate. Conclusions: Low-dose VD increased the survival rate, attenuated developmental retardation, and improved alveolarization and pulmonary vascularization arrest in hyperoxia-induced BPD partially by inhibiting NETs.